Exploring the Functions of Mutant p53 through TP53 Knockout in HaCaT Keratinocytes - Daniil Romashin; Alexander Rusanov; Viktoriia Arzumanian; Alexandra Varshaver; Ekaterina Poverennaya; Igor Vakhrushev; Alexander Netrusov; Nataliya Luzgina (Current Issues in Molecular Biology, 2024)
Approximately 50% of tumors carry mutations in TP53; thus, evaluation of the features of mutant p53 is crucial to understanding the mechanisms underlying cell transformation and tumor progression. HaCaT keratinocytes represent a valuable model for research in this area since they are considered normal, although they bear two gain-of-function mutations in TP53. In the present study, transcriptomic and proteomic profiling were employed to examine the functions of mutant p53 and to investigate the impact of its complete abolishment. Our findings indicate that CRISPR-mediated TP53 knockout results in significant changes at the transcriptomic and proteomic levels. The knockout of TP53 significantly increased the migration rate and altered the expression of genes associated with invasion, migration, and EMT but suppressed the epidermal differentiation program. These outcomes suggest that, despite being dysfunctional, p53 may still possess oncosuppressive functions. However, despite being considered normal keratinocytes, HaCaT cells exhibit oncogenic properties.